Isolasi dan Identifikasi Bakteri E-Coli dari Tumbuhan Coleus Amboinicus - Zinda Rizkia Aprilia; Ardi Mustakim (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Escherichia coli (E. coli) is an indicator bacteria that is often used to assess the level of microbial contamination in food and plants. This study aims to isolate and identify the presence of E. coli from Coleus amboinicus plants which are known to have antibacterial activity. Fresh leaf samples of C. amboinicus were taken from the home yard environment. Isolation was carried out using the serial dilution method and planting on eosin methylene blue (EMB) placement media. Identification was carried out based on colony morphology, Gram staining, and biochemical tests including IMViC (Indole, Methyl Red, Voges-Proskauer, Citrate). The results showed the presence of metallic green colonies on EMB, which showed the characteristics of E. coli. Biochemical tests showed Indole (+), Methyl Red (+), Voges-Proskauer (-), and Citrate (-), which confirmed the isolate as E. coli. The presence of E. coli in C. amboinicus indicates the possibility of environmental fecal contamination, and is a concern in the processing and consumption of this medicinal plant.